A Comparative Analysis of Cost-Effective Quantum Energy Plasma Technology: An FTIR Spectroscopic Investigation of Octa-H Gel Formulations and the Role of Silica Nanoparticles - Yehia, Hesham Mohamed Abd Al-Salam (European Journal of Applied Sciences, 2025)
The burgeoning field of advanced materials science continually seeks innovative technologies that offer enhanced efficacy coupled with economic viability. Among these emerging paradigms is the concept of "Quantum Energy Plasma" (QEP), a term often used in proprietary contexts to describe a state of matter or energy infusion purported to enhance material properties. This paper presents a comprehensive investigation into the cost-effectiveness of QEP technology as realized in three specific samples: Octa-H Gel, Octa-H Gel with Titanium, and Octa-H Gel Blue. The analysis is anchored in empirical data derived from a Fourier Transform Infrared (FTIR) spectroscopy report, which provides the molecular "fingerprint" of each formulation. By interpreting the detected absorption bands, we delineate the unique chemical compositions and functional groups present, linking them to the purported mechanisms of QEP. A central theme throughout this discussion is the role of Silica Nanoparticles (SiO₂ NPs), designated here as OCTA-H, which are posited as the fundamental scaffold enabling and stabilizing the QEP state. This paper compares the hypothesized QEP technology against conventional enhancement technologies, such as standard nanoparticle doping, chemical catalysts, and bulk material treatments, arguing that the Octa-H Gel platform represents a potentially superior cost-effective solution due to its scalable silica-based matrix, synergistic multi-component design, and targeted functionality as evidenced by spectroscopic data. The FTIR findings for Sample #1 (Octa-H Gel), Sample #2 (Octa-H Gel with Titanium), and Sample #3 (Octa-H Gel Blue) reveal distinct spectral signatures, confirming compositional modifications and providing a scientific basis for their differentiated performance and economic advantages.